2001
DOI: 10.1080/09515070125262
|View full text |Cite
|
Sign up to set email alerts
|

The anticipated future of counselling psychology in the United States: A Delphi poll

Abstract: A Delphi poll of the institutional members of the Council of Counselling Psychology Training Programmes in the United States revealed anticipations regarding the future of the speciality in relation to three broad areas of contemporary concern. These included the speciality's anticipated core identity, the future role of science and research training in the speciality, and its probable developments in relation to professional training. In general, a commitment to cultural diversity and life-span development oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…These results carry potential challenges as well as opportunities for the field of professional psychology and the mechanisms that are designed to support ongoing professional competence within it. On the one hand, the diminishing durability of knowledge may pose significant challenges in relation to generating and supporting the kinds of continued training and education needed to enable the field to keep pace with its rapidly developing and increasingly specialized knowledge base (Neimeyer, Taylor, Wear, & Linder-Crow, 2012). On the other hand, however, an awareness of the differential half-lives of knowledge across various areas of specialization may provide a kind of road map in relation to the areas of greatest need, allowing the field to use this information to make decisions about whether to concentrate its education and training resources (at the doctoral, postdoctoral, and continuing education levels) in the selected areas associated with the greatest knowledge advances or to redouble its attention to more durable domains of knowledge with slower rates of new knowledge development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results carry potential challenges as well as opportunities for the field of professional psychology and the mechanisms that are designed to support ongoing professional competence within it. On the one hand, the diminishing durability of knowledge may pose significant challenges in relation to generating and supporting the kinds of continued training and education needed to enable the field to keep pace with its rapidly developing and increasingly specialized knowledge base (Neimeyer, Taylor, Wear, & Linder-Crow, 2012). On the other hand, however, an awareness of the differential half-lives of knowledge across various areas of specialization may provide a kind of road map in relation to the areas of greatest need, allowing the field to use this information to make decisions about whether to concentrate its education and training resources (at the doctoral, postdoctoral, and continuing education levels) in the selected areas associated with the greatest knowledge advances or to redouble its attention to more durable domains of knowledge with slower rates of new knowledge development.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence supports Wise et al's (2010) observation. In a Delphi Poll of professional psychologists, which involved the iterative, confidential polling of an identified panel of designated experts, members of the panel predicted a 28% decrease in the overall half-life of knowledge within professional psychology over the course of the next 10 years (Neimeyer, Taylor, Wear, & Linder-Crow, 2012), meaning that newly minted doctoral graduates might be expected to experience significant, perhaps disconcerting, levels of knowledge obsolescence within a matter of only 6 or 7 years after their graduation.…”
mentioning
confidence: 99%
“…In addition to the increasing attention researchers are investing in enhancing human strengths such as forgiveness, theorists also increasingly advocate taking a developmental approach when working with clients (e.g., Ivey & Ivey, 1998). Indeed, attention to life‐span development has been a long‐standing core feature within specialties such as counseling psychology (Neimeyer & Diamond, 2001). Despite the recognized importance of developmental perspectives in counseling and the emerging research on the importance of forgiveness, little research has been done regarding the relationship between forgiveness and psychosocial development.…”
Section: Forgiveness and Erikson's Theory Of Psychosocial Developmentmentioning
confidence: 99%
“…Although the ability to forgive has been cited as a prosocial interpersonal process (Karremans, Van Lange, & Holland, 2005), with numerous emotional and health‐related benefits (Karremans et al, 2003; Lawler et al, 2005), and although counselors advocate using developmental perspectives in their work (Ivey & Ivey, 1998; Neimeyer & Diamond, 2001), little research has been conducted on the relationships among forgiveness, counseling, and human development. In the only study identified to date on this topic, Romig and Veenstra (1998) found a significant relationship between forgiveness and the successful resolution of Erikson's (1963) psychosocial crises.…”
Section: Forgiveness and Erikson's Theory Of Psychosocial Developmentmentioning
confidence: 99%
“…These views are then summarised by the researcher and returned to the same experts for further comments and additional views; this process continues until a consensus about the future has been reached. This latter method is extremely popular and has been widely used across a range of disciplines for the forecasting of future trends (see, for example, Fleming and Monda-Amaya, 2001;Neimeyer and Diamond, 2001;Norcross et al, 2002;Smith, 1997;Toward and Ostwald, 2002).…”
Section: Third Aim Of the Papermentioning
confidence: 99%